2011
DOI: 10.4161/cib.15369
|View full text |Cite
|
Sign up to set email alerts
|

Expression of individual mammalian Sun1 isoforms depends on the cell type

Abstract: Mammalian Sun1 belongs to an evolutionarily conserved family of inner nuclear membrane proteins, which are known as SUN domain proteins. SUN domain proteins interact with KASH domain partners to form bridging complexes, so-called LINC complexes, that physically connect the nuclear interior to the cytoskeleton. LINC complexes are critical for nuclear integrity and play fundamental roles in nuclear positioning, shaping and movement. The mammalian genome codes for at least five different SUN domain proteins used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
(27 reference statements)
1
24
0
Order By: Relevance
“…The amplicons were analyzed in 6% TBE polyacrylamide gels. Similar to mouse SUN1, 34 the shortest SUN1 variant, SUN1_702, could be detected exclusively in testis but not in any somatic tissues tested.…”
Section: Sun1 Splice Variants In Human Cellsmentioning
confidence: 81%
See 2 more Smart Citations
“…The amplicons were analyzed in 6% TBE polyacrylamide gels. Similar to mouse SUN1, 34 the shortest SUN1 variant, SUN1_702, could be detected exclusively in testis but not in any somatic tissues tested.…”
Section: Sun1 Splice Variants In Human Cellsmentioning
confidence: 81%
“…35 This variant, which is referred to as SUN1_916 in this report, corresponds to the largest mouse SUN1 variant, composed of 913 aa, that predominates in most mouse tissues. 34 In addition to well-known variants, we identified a novel SUN1 splice variant; SUN1_888, which encodes 888 aa (AB648918, Fig. 1A and B, and details in the Materials and Methods).…”
Section: Sun1 Splice Variants In Human Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two additional SUN1 isoforms are also expressed in testis. One of these is missing exon 7 (SUN17), while the other lacks exons 7 and 9 (SUN17,9, Figure S2A) (Göb et al, 2011). We raised an antibody against these two isoform by immunizing rabbits with a peptide spanning the exon 6-8 junction ( Figure S2A).…”
Section: This Mutant When Expressed In Hela Cells Efficiently Releasementioning
confidence: 98%
“…This view is reinforced by observations on the disposition of certain SUN1 splice isoforms that are also expressed during spermiogenesis. One of these, SUN1 lacks exons 7-10 ( Figure S2A) (Göb et al, 2011;Göb et al, 2010), which encode sequences within the SUN1 nucleoplasmic domain immediately adjacent to the transmembrane region. While exogenous SUN1 localizes largely to the NE in HeLa cells (see Figure 4C in the paper by (Liu et al, 2007)), in spermatids it is suggested to reside in the acrosomal membrane where it may act as a tether for Nesprin 3.…”
Section: This Mutant When Expressed In Hela Cells Efficiently Releasementioning
confidence: 99%